Formation and amplification of 50-ps pulses in a THL-100 hybrid laser system - Alekseev S. V. Sergey Vladimirovich; Ivanov N. G. Nikolay Georgievich; Losev V. F. Valery Fedorovich; Mesyats G. A. Gennady Andreyevich; Mikheev L. D. Leonid Dmitrievich; Panchenko Yu. N. Yury Nikolaevich; Ratakhin N. A. Nikolay Aleksandrovich; Yastremsky A. G. Arkady Grigorjevich (2017, 2017)
Title screen